63.9k views
2 votes
F the value of x decreases by 6, how does the value of m(x + 9) change?

User Brian Hong
by
5.3k points

1 Answer

4 votes

start with y= m(x+9)

Use the distributive property:

y= mx+9m

Now you want x to decrease by 6:

so y ' = m(x-6) + 9m

Use distributive property again:

y'= mx - 6m + 9m

y' = (mx+9m) - 6m

y' = y - 6m

So the value of y decreases by 6m.

User John Fu
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.